Efficacy of an oral narrative language intervention program on children with hearing impairment: a randomized controlled trial - Sara Ibrahim; Ossama Sobhy; Riham El-Maghraby; Nesrine Hamouda (The Egyptian Journal of Otolaryngology)
Abstract Background Children with hearing impairment have less opportunities for adequate language exposure which results in delayed narrative and discourse language development. Previous intervention studies have mainly focused on the early developing language forms, with little focus on narrative intervention. The aim of the current study was to develop the Oral Narrative Language Intervention Program (ONLIP) and detect its efficacy on improving narrative and linguistic skills of HI children in comparison to conventional language and auditory training. The randomized controlled study was conducted on 44 children with sensorineural hearing loss. The subjects were randomly divided by block randomization into two groups: group A (cases) which received training with the ONLIP and group B (control) which received conventional intervention for 3 months. The participants were evaluated pre- and post-intervention by the Arabic version of the Test of Narrative Language — Second Edition (TNL-2) and the Comprehensive Arabic Language Test (CALT). Results A statistically significant improvement was found in all of the assessed narrative comprehension and production skills, as well as the composite performance in the HI cases group when both groups were compared post-therapy. A statistically significant improvement was found in both groups when the scores for the CALT were compared between pre- and post-intervention. Conclusions ONLIP is an effective tool in improving the narrative skills of HI children in comparison to conventional training. Both forms of intervention are effective in improving linguistic form and structure.